2016
DOI: 10.1007/s13593-016-0372-z
|View full text |Cite
|
Sign up to set email alerts
|

Biochar to improve soil fertility. A review

Abstract: Soil mineral depletion is a major issue due mainly to soil erosion and nutrient leaching. The addition of biochar is a solution because biochar has been shown to improve soil fertility, to promote plant growth, to increase crop yield, and to reduce contaminations. We review here biochar potential to improve soil fertility. The main properties of biochar are the following: high surface area with many functional groups, high nutrient content, and slow-release fertilizer. We discuss the influence of feedstock, py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
348
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 799 publications
(432 citation statements)
references
References 133 publications
11
348
0
6
Order By: Relevance
“…Similar results of adsorption using biochar and adsorbents for NH 4 -N have been described for ion-exchange resins [19], zeolites [20], and activated carbon [21]. This result implies that the biochar pellet can play an important role as an absorbent of NH 4 -N when applied in cropland.…”
Section: Adsorption and Removal Rates Of Nh 4 -N From The Biochar Pelsupporting
confidence: 78%
See 4 more Smart Citations
“…Similar results of adsorption using biochar and adsorbents for NH 4 -N have been described for ion-exchange resins [19], zeolites [20], and activated carbon [21]. This result implies that the biochar pellet can play an important role as an absorbent of NH 4 -N when applied in cropland.…”
Section: Adsorption and Removal Rates Of Nh 4 -N From The Biochar Pelsupporting
confidence: 78%
“…The corresponding isotherm parameters are presented in Table 5. It was observed that the Langmuir adsorption capacity of the biochar pellet for NH 4 -N was 2.94 mg g −1 . Table 4 shows the amount of NH 4 -N adsorbed at equilibrium (q e ) at the slope and intercept, rate constants (K 1 and K 2 ) of the kinetic models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations